Hong Kong Children’s School Readiness in Times of COVID-19: The Contributions of Parent Perceived Social Support, Parent Competency, and Time Spent With Children - Lau, Eva Yi Hung; Li, Jian-Bin (Frontiers in Psychology, 2021)
School readiness is an important but challenging issue of child development, especially during COVID-19 when most of the traditional offline activities that could promote school readiness (e.g., on-site visit) have been cancelled. There is a gap between the knowledge needed to promote children’s school readiness in times of pandemic and the limited understanding of this topic so far. This gap could be particularly concerning in the social contexts where examinations are stressed and educational competition is high (e.g., Hong Kong). In this study, we examined how well children were ready for primary school, the extent to which parent perceived social support was related to children’s school readiness, and whether parent competence and their time spent with children would moderate the said link. A cross-sectional design survey with total population sampling (supplemented with convenience sampling) was conducted. Massive e-mails were sent to all kindergartens in Hong Kong inviting them to join the study by distributing the survey link to the parents of their K3 students. A total of 643 Hong Kong parents whose children were about to transition to primary school (87.1% mother) participated, answering measures specifically designed for this study online about how well they thought their children were ready for school, their competence to help with children’s school transition, and how much time they spent with children. Data were analyzed with PROCESS macro (model 3) in SPSS. Results found that most parents considered that their children were not fully ready for school, especially in terms of academic skills, self-management, and mental preparation. Furthermore, moderation analyses showed that after controlling for a number of demographic variables, parent perceived social support was positively related to better school readiness in children and this link was jointly moderated by parent competence and time spent with children. Specifically, children were rated most ready when parent perceived stronger social support, felt more competent, and spent more time with children. By contrast, the link between perceived social support and children’s school readiness was insignificant for parent who felt more competent but spent less time with children. Implications of how to enhance children’s school readiness are discussed.